Modernisasi Sistem Pendidikan Pesantren Salafiyah - Nur Hidayah (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
Pondok Pesantren has an effective role to form the character of human who have the characteristic and have Islamic values ​​through transformation process of yellow book. Pesantren is a very important link for the transformation of science and the inheritance of Islamic values ​​from the next generation of generation. Originally boarding school more known as Islamic educational institutions, the institutions used for the spread and study of Islam. Pondok Pesantren is an Islamic educational institution that puts the figure of Kyai as the central figure and the mosque as the center of the institution. The quality of pesantren education depends on the quality of kyai as social actors, mediators, dynamists, catalysts, motivators as well as power with the depths of kyai knowledge and new insights . Because with new insights a kyai will quickly anticipate the existence of an opinion that says that the output of boarding school students is not qualified, then kyai anticipate the changes in all fields according to the needs of the community